KAJIAN EFEK ALFA-PINEN TERHADAP i-NOS (INDUCIBLE NITRIC OXIDE SYNTHASE) PADA KULTUR SEL NEURON-GLIA YANG DIPAPAR LIPOPOLISAKARIDA - Krisna Murtyastami, Sri Widyarti, Khusnul Khotimah (Universitas Muhammadiyah Malang, 2010)
The aim of this research was to study the effect of a-pinene on number of cell that express iNOS (inducible Nitric Oxide Synthase) on lipopolysaccharide (LPS)-induced neuron-glial culture. Neuron-glial culture were divided into eight groups: (1) normal; (2), (3) and (4) incubated with a-pinene (0,2; 0,4 and 0,8 μg/mL respectively, for 24 hours); (5) incubated with LPS 1 μg/mL; (6), (7) and (8) incubated with a-pinene (0,2; 0,4 and 0,8 μg/mL respectively, for 24 hours) and then induced with LPS (1 μg/mL, on 1 last hour of treatment period). The expression of iNOS in neuron-glial culture was detected by immunocytochemistry using anti-iNOS rabbit polyclonal IgG and goat anti-rabbit IgG Biotin Conjugated. The result shown that iNOS were expressed on normal group. Lipopolysaccharide 1 μg/mL induction causing iNOS expression increased approximately three times higher than normal (from 9,7% became 28,7%). Inducible NOS expression on non LPS-induced neuron-glial culture did not affected by a-pinene. Whereas a-pinene 0,2 and 0,4 μg/mL could suppress iNOS expression on LPSinduced condition. a-pinene 0,2; 0,4 and 0,8 μg/mL could help neuronglial cells survived on LPS-induced condition, but normal neuron-glial culture’s density was decreased when incubated with a-pinene 0,8 μg/mL. Keywords: alpha-pinene, cell culture, glial, iNOS, LPS, neuron